2007
DOI: 10.1159/000104875
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Renin mRNA Expression by Paricalcitol and Calcitriol in C57/BL6 Mice

Abstract: Background/Aims: Vitamin D receptor activators (VDRAs) may suppress renin expression and VDR-mediated renin inhibitors may offer a novel mechanism to control the RAS. Methods: We delineated the effects of paricalcitol and calcitriol on PTH, renin, and iCa2+ in C57/BL6 mice administered vehicle, paricalcitol, or calcitriol (0.01, 0.03, 0.10, 0.33, 1.0 µg/kg s.c.) 3 days/week for 9 days. Results: Paricalcitol produced PTH suppression from 0.03 to 1.0 µg/kg (values between 9.7 ± 3.3 and 20.7 ± 4.7 pg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…To test this concept, in the current study we treated a mouse model of diabetic nephropathy with a combination of losartan and paricalcitol. Paricalcitol (19-nor-1,25-dihydroxyvitamin D 2 ) is an activated vitamin D analog and activates VDR with a high affinity, and we used paricalcitol because it suppresses renin expression in mice with the same potency as calcitriol but without induction of hypercalcemia (31). Our data demonstrated that the combination of an ARB and a vitamin D analog markedly ameliorated renal injury because of more effective inhibition of the RAS within the kidney.…”
mentioning
confidence: 75%
“…To test this concept, in the current study we treated a mouse model of diabetic nephropathy with a combination of losartan and paricalcitol. Paricalcitol (19-nor-1,25-dihydroxyvitamin D 2 ) is an activated vitamin D analog and activates VDR with a high affinity, and we used paricalcitol because it suppresses renin expression in mice with the same potency as calcitriol but without induction of hypercalcemia (31). Our data demonstrated that the combination of an ARB and a vitamin D analog markedly ameliorated renal injury because of more effective inhibition of the RAS within the kidney.…”
mentioning
confidence: 75%
“…The vehicle group received vehicle injections using the same schedule. The pharmacological dosages were chosen based on previous reports (4,6,15). The surgical procedures were performed as described in previous studies (16,52).…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…[5][6][7] Recently, it has been shown that paricalcitol has anti-oxidant effects on renal tissue and suppresses the reninangiotensin system (RAS) in diabetic kidney. 8,9 Fryer et al 10 demonstrated that paricalcitol suppresses renal renin expression. It has also been recently reported that the combination of paricalcitol and enalapril treatment ameliorates oxidative injury by suppressing reactive oxygen species generating enzyme NADPH oxidase activity and by up regulating the antioxidant defense system in a uremic rat model of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%